Regional Impact Analysis of Carbon Tax Implementation on Indonesia’s Coal Power Plant with Interregional Input-output Method - Kamil, Ahmad Syafiq; Setyaningrum, Lindri; Lesmana, Ade Chandra; Putri, Megawati Suharsono; Negara, Syandi; Susiati, Heni; Anggoro, Yohanes Dwi (International Journal of Energy Economics and Policy, 2023)
The excessive use of greenhouse gases (mainly carbon dioxide) causes a global emission of greenhouse gases. This has eventually brought climate change and global warming, that will affect the human life standard. Also it has several economical impacts such as increasing the mitigation budget for anticipating the climate change problems by applying a carbon tax as one of strategies to reduce carbon emissions. Carbon tax is one of additional economic instrument and has high possibility to be implemented in Indonesia to help its future low carbon development especially on energy sector. Under such a circumstance, this paper aims to predict the possible impact of implementing a carbon tax implementation on Coal Power Plant (CPP) and revenue recycling for 6 regions in Indonesia i.e. Sumatera, Jawa, Bali and Nusa Tenggara, Kalimantan, Sulawesi, Maluku and Papua. The IRIO (InterRegional InputOutput) model of six regions in Indonesia has been developed based on the Central Bureau of Statistics with seventeen sectors in 2016 to evaluate the impact of carbon taxes with a carbon price of 2,1 USD/ton on CPP and to show the scenarios for the distribution impact of carbon tax revenues on output, wages, and GRDP. The results show the implementation of a carbon price of e 2.1USD/ton will give extra revenue of around 241 Billion Rupiah nationally with the distribution of 73%, 15%, 7%, 3%, 2%, and 1% from Java, Sumatera, Kalimantan, Bali-Nusa Tenggara, and Maluku-Papua, respectively. Through revenue recycling, those values could increase the total output, wages, and GDRP per region by around 451, 100, and 169 Billion Rupiah, respectively. The revenue recyling option and its economic impact for each 17 sectors are also identified in the study with spesific characteristics for each region. In conclusion, the result could help the government determine its climate change mitigation strategy, so it could boost the regional economy. Based on the study results, this paper recommends the government to conduct an intensive monitoring and evaluation on low carbon policies for CPP in Java and Sulawesi.